2020
DOI: 10.3389/fpsyt.2020.586686
|View full text |Cite
|
Sign up to set email alerts
|

Delirium: Clinical Presentation and Outcomes in Older COVID-19 Patients

Abstract: The aim of the study is to describe the clinical characteristics and outcomes of a series of older patients consecutively admitted into a non-ICU ward due to SARS-CoV-2 infection (14, males 11), developing delirium. Hypokinetic delirium with lethargy and confusion was observed in 43% of cases (6/14 patients). A total of eight patients exhibited hyperkinetic delirium and 50% of these patients (4/8) died. The overall mortality rate was 71% (10/14 patients). Among the four survivors we observed two different clin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
19
0
5

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(27 citation statements)
references
References 20 publications
3
19
0
5
Order By: Relevance
“…In a review of mortality risk factors among older adults with COVID-19, Sun et al (2020) reported a significantly higher percentage of consciousness disorders among patients who died in comparison to those who were discharged. One of the patients described here presented with altered mental status and lethargy, a manifestation of hypoactive delirium similar to other reported CNS manifestations of COVID-19 ( Rozzini et al, 2020 ). Lethargy is a pathological state of sleepiness or deep unresponsiveness and inactivity in contrast to fatigue which manifests as a lack of energy and motivation and has been described in up to 44% of patients with COVID-19 ( Huang et al, 2020 ; Zhu et al, 2020 ).…”
Section: Discussionsupporting
confidence: 81%
“…In a review of mortality risk factors among older adults with COVID-19, Sun et al (2020) reported a significantly higher percentage of consciousness disorders among patients who died in comparison to those who were discharged. One of the patients described here presented with altered mental status and lethargy, a manifestation of hypoactive delirium similar to other reported CNS manifestations of COVID-19 ( Rozzini et al, 2020 ). Lethargy is a pathological state of sleepiness or deep unresponsiveness and inactivity in contrast to fatigue which manifests as a lack of energy and motivation and has been described in up to 44% of patients with COVID-19 ( Huang et al, 2020 ; Zhu et al, 2020 ).…”
Section: Discussionsupporting
confidence: 81%
“…COVID-19 patients with dementia may be hospitalized due to the characteristic symptoms of the infection (pneumonia, fever, respiratory failure). However, deterioration of functional status, behavioural symptoms, and in about two-third of cases, delirium, especially in the hypoactive form, are the most frequent symptoms of COVID-19 among patients affected by dementia [33].…”
Section: Delirium In Covid-19 Patients With Dementiamentioning
confidence: 99%
“…Some of these manifestations include delirium, cognitive impairments, mood alterations, anxiety disorders, depression, suicidal ideations, post-traumatic stress disorder (PTSD), insomnia, psychosis, and schizophrenia (Brown et al, 2020;Keyhanian et al, 2020;Mazza et al, 2020). In other clinical reports, COVID-19 patients have been shown to develop hypokinetic delirium (Rozzini et al, 2020). Self-rated symptoms in the psychopathological range include 30% for PTSD, 40% for depression, 40% for anxiety, 20% for obsessive-compulsive disorder symptoms, and 40% for insomnia (Mazza et al, 2020).…”
Section: Psychiatric Manifestationsmentioning
confidence: 99%